Dynamic variability in speech: a forensic phonetic study of British English, 2006-2007 - Nolan, Francis (UK Data Service, 2011)
The aim of the DyViS database is to provide a database of 100 speakers of similar age and with the same accent, primarily with a view to studying variation in personal voice characteristics untrammelled by accent variation. Such a resource has applications in forensic phonetic research, but will also be useful for studying many linguistic aspects of speech. The speakers are all male, aged between 18 and 25 years, and selected as speakers with Standard Southern British English (SSBE) pronunciation. In order to elicit some of the range of variation a voice may exhibit, the speakers were recorded doing four tasks. In the first, they took part in a simulated police interview based on a crime, the details of which were supplied to them as they were interviewed. Some of the information, being incriminating within the imaginary scenario, had to be denied. In the second, the speaker engaged in a telephone conversation with an 'accomplice'. Both these tasks provide extensive examples of spontaneous conversation. The telephone call was recorded simultaneously direct and over a landline, allowing acoustic comparisons to be made. Speakers also read a text, and sentences containing target words. A subset of 20 returned over a month later to re-record non-contemporaneous versions of the reading tasks.